2019
DOI: 10.4274/jtgga.galenos.2019.2019.0029
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic assisted robotic myomectomy of a huge myoma; Does robotic surgery change the borders in minimally invasive gynecology?

Abstract: Today, the adoption of minimal invasive gynecologic procedures is expanding their routine use in clinical practice. Until recently, a diameter of 8 cm was the recommended maximal size for laparoscopic removal of fibroids. However, robot-assisted laparoscopy improved the capacity and the feasibility of the many gynecologic procedures. Here, we report a video of robotic myomectomy of a huge myoma. (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“… 2 4 Minimally invasive myomectomy (MIM) is feasible even in cases with large fibroids. 5 Although the use of MIS hysterectomy, has increased, 6 there is still little data regarding overall utilization of MIM. Most existing data come from studies exploring changes in practice after the FDA power morcellation recommendation.…”
Section: Introductionmentioning
confidence: 99%
“… 2 4 Minimally invasive myomectomy (MIM) is feasible even in cases with large fibroids. 5 Although the use of MIS hysterectomy, has increased, 6 there is still little data regarding overall utilization of MIM. Most existing data come from studies exploring changes in practice after the FDA power morcellation recommendation.…”
Section: Introductionmentioning
confidence: 99%
“…Surgery is widely used in clinical treatment, and mainly involves myomectomy or hysterectomy, including myomectomy through hysteroscopy, myomectomy through open or laparoscopy, uterine artery embolization, and interventions to induce thermal ablation of UFs under radiological or ultrasound guidance ( 21 ). Among them, LM has been widely used in clinical practice owing to its small abdominal wall incision, aesthetics, minimal trauma, and faster postoperative recovery ( 22 , 23 ). However, regardless of the treatment method, complications such as postoperative bleeding, recurrence or complications of urological diseases, and even adverse effects on fertility may still occur after treatment ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a case report published in 2015, a 17-cm myoma was successfully removed with laparoscopic myomectomy [ 1 ]. In addition, Takmaz et al [ 6 ] also reported a case of successful removal of a 16-cm-sized myoma using RALM in 2019. In a previous retrospective study [ 7 ], it was asserted that the size of myoma that can be excised by laparoscopy may be limited to less than 8 cm or 10 cm.…”
Section: Discussionmentioning
confidence: 99%